Standar Proses dan Implementasi Kurikulum Merdeka - Oies Febria Siskawati; Husna Fikria; Fadriati Fadriati (Journal on Education, 2024)
The curriculum has an important role in the educational process, the growing needs of society make the curriculum dynamic. In 2024 the government officially announces that the independent curriculum will become the national curriculum. This research aims to analyze the independent curriculum further by focusing on learning process standards, namely planning, implementation and assessment through a systematic literature review. The results show that the implementation of the independent curriculum faces a number of challenges and obstacles, such as significant changes in the way teachers teach, especially with the presence of new elements such as the Project for Strengthening the Pancasila Student Profile. This research proposes several steps for improvement, including training for teachers in various learning strategies, increasing coordination between all related parties, and increasing teacher professional competence in utilizing the Merdeka Mengajar Platform (PMM). The conclusions of this research emphasize the need for continuous efforts to improve the quality of learning through teacher training, utilization of resources such as PMM, and collaboration between all relevant parties